2023
DOI: 10.1111/eve.13807
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and unsuccessful management of iatrogenic fungal septic arthritis caused byWickerhamomyces anomalous(formerlyCandida pelliculosa) and concurrent osteochondral lesion in Ireland

Abstract: Summary Equine septic fungal arthritis is poorly documented in the literature. There is an absence of efficacy and safety data for antifungal medications, highlighting the importance of documenting this case. A 15‐year‐old Irish sport horse gelding presented 4/5 (AAEP) left hindlimb lame 13 days after intra‐articular medication of the left tarsocrural joint with triamcinolone and hyaluronic acid. Radiography revealed an osteochondral fragment at the distal intermediate ridge of the tibia and shallow subchondra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…One scientific article contributed with information related to animal safety concerns: Duggan et al (2023) reported a case in Ireland of a horse with problems in the left tarsocrural joint. After arthroscopic lavage and a subsequent operation of the joint, the horse was ultimately diagnosed with an infection with W. anomalus.…”
Section: Wickerhamomyces Anomalusmentioning
confidence: 99%
“…One scientific article contributed with information related to animal safety concerns: Duggan et al (2023) reported a case in Ireland of a horse with problems in the left tarsocrural joint. After arthroscopic lavage and a subsequent operation of the joint, the horse was ultimately diagnosed with an infection with W. anomalus.…”
Section: Wickerhamomyces Anomalusmentioning
confidence: 99%